1984
DOI: 10.1007/bf00546707
|View full text |Cite
|
Sign up to set email alerts
|

Acetylator phenotypes: Effect of age

Abstract: The distribution of acetylator phenotypes in a Hungarian population of 253 Caucasian was studied. The patients were divided into two age groups - the elderly over 60 years, and young below that age. The individuals below the age of 60 years contained an equal proportion of the two acetylator phenotypes. The same distribution was observed in the population as a whole. In the elderly subjects the slow acetylator phenotype was predominant. The finding supports the hypothesis that age has an influence on hepatic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Although it is recognised that the activities of hepatic microsomal enzymes are modulated by factors such as age, sex, diet, disease, medication and environmental exposures (Vesell, 1982) little is known about the influence of such factors on NAT activity. Recently several studies have given contradictory results on the influence of age and sex on the acetylation phenotype (Gachalyi et al, 1984;Paulsen & Nilsson, 1985;Pontiroli et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is recognised that the activities of hepatic microsomal enzymes are modulated by factors such as age, sex, diet, disease, medication and environmental exposures (Vesell, 1982) little is known about the influence of such factors on NAT activity. Recently several studies have given contradictory results on the influence of age and sex on the acetylation phenotype (Gachalyi et al, 1984;Paulsen & Nilsson, 1985;Pontiroli et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Our patient population was comparatively young, and this could be the reason why our results differ from a study conducted by Paulsen & Nilsson (23). Similarly, another study showed a predominance of slow acetylator phenotype in ages above 60 (24). Similarly, another study showed a predominance of slow acetylator phenotype in ages above 60 (24).…”
Section: Discussionmentioning
confidence: 78%
“…In this study, males, especially in old age, were significantly slower than females. Similarly, another study showed a predominance of slow acetylator phenotype in ages above 60 (24). Acetylator phenotypes show wide variations in different ethnic groups around the world (4, 21).…”
Section: Discussionmentioning
confidence: 89%
“…Die Auswahl der Patienten beruhte auf der Grundlage, daß ihr Alter und Körpergewicht annähernd identisch waren. Es ist bekannt, daß sich das Verhältnis der langsamen Azetylierer über 60 Jahre erhöht (13), das zwischen 24 und 46 Jahre liegende Alter der in die Untersuchung einbezogenen Patienten konnte jedoch die den Metabolismus eventuell beeinflussende Wirkung des Alters sicherlich ausschließen. Infolge des zwischen 58 und 73kg betragenden Körpergewichts der Patienten war die Dosismenge je Körpergewicht-Kilogramm in sämtlichen Fällen annähernd gleich groß, täglich 2g SASP durchschnittlich entsprach einer Dosis von 30 mg/kg Körpergewicht.…”
Section: Patienten Und Methodikunclassified